“Effects of flap modification on third molar extraction outcomes”-A randomised split mouth study - Geetha Sridharan; Komagan Prabhu Nakkeeran; Gnanam Andavan; Krishna Kumar Raja V.B (Journal of Oral Biology and Craniofacial Research)
Aim: The main purpose of this experimental study was to compare whether modifications in flap design influence the post-operative outcome of third molar surgeries. Materials and methods: This study was designed as a randomized, single-blinded,split-mouth cross-over comparative study. The predictor variables were the flap type; Conventional Ward's was used to expose the tooth with a difference in the anterior release incision between the groups.Oblique anterior releasing incision and vertical anterior releasing incisions were used for the control and study group respectively.The primary outcome variables were pain measured using VAS (Visual analogue scale), swelling in mm; mouth opening measured in mm, periodontal probing depth in a mm, wound healing by modified Landry's score and surgical accessibility. Statistical significance was set at 5% (α = 0.05). Result: Twenty five patients with bilateral, mirror-image impacted mandibular third molars participated in the study.The study group was associated with moderate swelling that was not statistically significant. .The outcome variables i.e. pain, wound healing, mouth opening, and periodontal pocket depth had no statistical difference on comparing the two groups. In terms of accessibility, the control group was found to be better with the statistical significance of p = 0.00184. Conclusion: Modifying conventional Ward's design influences the degree of swelling and surgical accessibility. Vertical anterior releasing incision in conventional Ward's has no advantage over conventional Ward's with oblique anterior releasing incision.